From Newton’s fluxions to virtual microscopes - Bair, Jacques; Henry, Valerie (Teaching Mathematics and Computer Science, 2007)
The method of fluxions was originally given by Newton among others in order to determine the tangent to a curve. In this note, we will formulate this method by the light of some modern mathematical tools: using the concept of limit, but also with hyperreal numbers and their standard parts and with dual numbers; another way is the use of virtual microscopes both in the contexts of classical and non standard analysis.